The Antarctic - King, H. G. R.; Hargreaves, Pat. (London : Blandford Press, 1969)
Depicts the geological history, discovery and exploration, plant and animal life, and resources of Antarctica, and discusses treaties pertaining to it. Includes glossary.
Includes index.
Bibliography: p. 68.
Keywords: Antarctica -- Juvenile literature; Antarctica